Cervical and axial dystonia secondary to mirtazapine: a case report and literature review - Jamir Pitton Rissardo (Annals of Movement Disorders, 2020)
Mirtazapine (MTZ) is an atypical antidepressant frequently prescribed for the management of major depressive disorder. It has multiple mechanisms of action, which probably contribute to the several side effects encountered with this medication. Hyperkinetic movement disorders induced by MTZ have been rarely reported in the literature. To the best of authors’ knowledge, there are five cases of dystonia (DTN) secondary to MTZ use, but this study reports the youngest individual in a nonpsychiatric MTZ indication. We report a case of an adult woman who presented with axial and cervical DTN-type laterocollis after 5 days of MTZ use, which was indicated for hot flashes. A comprehensive review of the cases and a mechanism assumption are performed.